قواعــد العرف الفقهية عند بن قيم الجوزية - Mahasin Zuhair Thaher; Abedllah Ali Alsafee (البصيرة: مجلة الدراسات الإسلامية, 2023)
This research raises the subject of fiqh rules regarding customs according to Ibn Qayyim al-Jauziyyah with the aim of revealing the current fiqh rules regarding customs according to Ibn al-Qayyim, mentioning the implementation of these rules in fiqh matters, and determining in what fields of jurisprudence these rules can be implemented. This research uses inductive, analytical, and applied approaches. The research results show several things. First, the disclosure of the main rules regarding customs, which were considered final by Ibn al-Qayyim in his ijtihad, and in general, there are three rules, namely: the rule "requirements based on custom are the same as oral requirements", the rule "permission based on custom is the same as permission based on verbal", and the rule "anything that is not specified in the Shari'a or language, the determination is returned to custom. Second, the many implementations of fiqh rules regarding customs in Ibn al-Qayyim's book show that he used these rules as a source of advice and suggestions in istinbat. Third, Ibn al-Qayyim applied many fiqh rules regarding customs in the field of muamalah fiqh.